Breaking barriers: how the rural poor engage in tourism activities without external support in selected Iranian villages - Torabi, Zabih-Allah (Frontiers in Sustainable Tourism, 2024)
This study investigates the participation of the rural poor in tourism activities in selected villages in Shahrud, Iran, addressing the lack of research on their direct involvement in formal and informal tourism businesses. Through qualitative methods and face-to-face interviews, the experiences of disadvantaged individuals in Qalae Bala, Abar, and Reza Abad villages are examined. Findings suggest that despite minimal external support, the rural poor actively engage in tourism by seeking formal employment, participating in informal activities, and acquiring relevant knowledge and skills. The study highlights the potential for informal tourism businesses to increase opportunities for people experiencing poverty. These insights contribute to a more comprehensive understanding of the field, and the implications for policy and practice are discussed. The study emphasizes the importance of considering both formal and informal tourism activities when exploring the role of tourism in poverty alleviation and the need for targeted interventions to support the rural poor's participation in the tourism sector.